How traditional manufacturers succeed in D2D: A strategic framework for assortment and pricing to solve channel conflicts - Constantin Götsch; Simon Rupprecht; Tobias Kuntner; Eva Anderl (Marketing Review St.Gallen, 2023)
D2C offers the chance for traditional manufacturers to gain independence and reduce margin pressure by bypassing retailers. A differentiated assortment and pricing approach is a key lever for mitigating the resulting risk of channel conflicts. Our research helps manufacturers succeed in D2C by delivering a framework that provides actionable differentiation strategies within a four-phase maturity model.
Keywords: 650